Analysis of predictors of malnutrition in adult hospitalized patients: social determinants and food security - Ouaijan, Krystel; Hwalla, Nahla; Kandala, Ngianga-Bakwin; Abi Kharma, Joelle; Kabengele Mpinga, Emmanuel (Frontiers in Nutrition, 2023)
Background: Malnutrition in hospitalized patients is becoming a priority during the patient care process due to its implications with worsening health outcomes. It can be the result of numerous social factors beyond the clinical ones. This study aimed to evaluate the link between these various risk factors considered as social determinants of health, food security levels, and malnutrition, and identifies potential predictors. Methods: A cross sectional observational study was conducted on a random sample of adult patients in five different hospitals in Lebanon. Malnutrition was assessed using the Global Leadership Initiative on Malnutrition (GLIM) criteria. Patients were interviewed to collects social and economic characteristics, categorized into four criteria: (1) area of residence (urbanization level), (2) level of education, (3) employment status and (4) source of health coverage. Food security level was screened by a validated two question-tool, adapted from the US Department of Agriculture Household Food Security Survey, targeting both quantity and quality. Results: In a random sample of 343 patients, the prevalence of malnutrition according to GLIM criteria was 35.6%. Patients with low level of food security, mainly low quality of food, had higher odds of being malnourished (OR=2.93). Unemployed or retired patients and those who has only reached elementary school had higher odds of being malnourished as compared to those employed or had university degrees respectively (OR=4.11 and OR=2.33 respectively). Employment status, education level and type of health coverage were identified as predictors of malnutrition in the multiple regression model. Household location (urban versus rural) was not associated with malnutrition. Conclusion: The social determinants of health identified in our study, mainly level of education and income level, in addition to the food security, were identified as predictors of malnutrition in hospitalized patients. These findings should guide healthcare professionals and national policies to adopt a broader perspective in targeting malnutrition by including social determinants in their nutrition care.